Predicting empty body weight in Pelibuey and Katahdin suckling lambs - Chay-Canul, A. J.; Salazar-Cuytun, E. R.; Robertos, N. F. Ojeda; Garcia-Herrera, R. A.; Chizzotti, M. L.; Almeida, A. K. [UNESP] (Wageningen Acad Publ, 2019)
The objective of the present study was to evaluate the relationship between body weight (BW) at slaughter (SBW) and empty body weight (EBW) and develop equations to estimate EBW in suckling hair lambs from different genotypes (Pelibuey and Katahdin), sexes (males and females) and litter sizes (single or double). The experiment was conducted with 66 lambs, 39 Pelibuey and 27 Katahdin, 37 males and 29 females; 30 of single birth and 36 of double birth. The effects of the genotype, sex and litter size were tested. The correlation coefficient between the SBW and EBW was 0.98 (P<0.001). It was observed that genotype and sex had no effect (P>0.05) on the relationship of SBW and EBW; however, the litter size did have influence (P<0.05) SBW and EBW relationship. The slopes of the equations were similar (P>0.001). Finally, an equation without intercept was proposed: EBW = 0.89 (+/- 0.003**) x SBW (R-2=0.98, MSE=0.119, RSD=0.345 and n=66). The present study indicates weight of gastrointestinal content was 11% of SBW of suckling hair lambs. The genotype, sex and litter size had no effect on this proportion.
Keywords: hair lambs; gastrointestinal content; sheep requirements; tropical regions